What is thyroid function in your just-diagnosed cancer patient? - Hercbergs, Aleck; Mousa, Shaker A.; Lin, Hung-Yun; Davis, Paul J. (Frontiers in Endocrinology, 2023)
The principal hormonal product of the thyroid gland, L-thyroxine (T4), is a prohormone for 3,3',5-triiodo-L-thyronine, T3, the major ligand of nuclear thyroid hormone receptors (TRs). At a cell surface thyroid hormone analogue receptor on cancer cell endothelial cell plasma membrane integrin alphavbeta3, however, T4 at physiological concentrations is biologically active and is the major ligand. At this site in solid tumor cells, T4 nongenomically initiates cell proliferation, is anti-apoptotic, supports radioresistance and enhances cancer-related angiogenesis. T4 also blocks anti-tumor T cell immune response against cancer cells. In contrast, hypothyroidism has been reported clinically to slow tumor growth. At physiological levels, T3 is inactive at the integrin and clinical maintenance of euthyroidism with T3 in cancer patients may slow tumor cell proliferation. We raise the possibility that host serum T4 levels in the upper tertile of the normal range may contribute to aggressive tumor behavior. Tumor metastasis and tumor-linked thrombosis may be due to upper tertile of the normal range concentrations of T4. That reverse T3 (rT3) may stimulate tumor growth has also been reported recently and thus the utility of adding this measurement to thyroid function testing requires assessment. In summary, T4 at physiological concentrations promotes tumor cell division and euthyroid hypothyroxinemia arrests clinically advanced solid tumors. These findings support the clinical possibility that circulating T4 levels in the upper tertile of the normal range require examination as a tumor supporting factor.